Strengthen "the sustainable farm" concept via efficacious conversion of farm wastes into methane. (December 2021) - Tawfik, Ahmed; Hassan, Gamal K.; Awad, Hanem; Hassan, Marwa; Rojas, Patricia; Sanz, Jose L.; Elsamadony, Mohamed; Pant, Deepak; Fujii, Manabu
Graphical abstract: Highlights: Livestock wastewater is essential for efficacious anaerobic digestion of farm wastes. Highest methane production was acquired at agriculture straws load of 20 g/300 mL. Maximum enzyme activities were noticed in the reactor achieved maximum methane yield. Digestate of the mixture was rich with ammonia, phosphorus, and trace metals. Phenol-degrading bacteria emerged after anaerobic digestion process. Abstract: With escalating global demand for renewable energy, exploitation of farm wastes (i.e., agriculture straw wastes (ASWs), livestock wastewater (LW) and sewage sludge (SS)) has been considered to attain maximum methane yield (MY) via anaerobic digestion (AD). Results pointed that mixture of SS and LW as anaerobes' source with 20 g of ASWs/300 mL of working volume achieved maximum MY and volatile solid (VS) removal efficiency of 0.44 (±0.05) L/gVS and 51.4 (±4.1)%, respectively. This was mainly because of emerging heavy duty bacterial species (i.e., Syntrophorhabdaceae and Synergistaceae ) and archaeal community (i.e, Methanosarcina and Methanoculleus ) after 70 days of anaerobic incubation. This was acquired along with boosting enzymatic activity, especially xylanase, cellulase and protease up to 71.5(±7.9), 179.3(±14.3) and 207.2(±16.2) U/100 mL, respectively. Furthermore, the digestate contained high concentrations of NH4 + (960.1±(76.8) mg/L), phosphorus (126.3±(10.1) mg/L) and trace metals, making it a good candidate as organic fertilizer.